2013
DOI: 10.1039/c3nr33403a
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient inhibition of human immunodeficiency virus type 1 reverse transcriptase by aptamers functionalized gold nanoparticles

Abstract: We have developed aptamer (Apt)-conjugated gold nanoparticles (Apt-Au NPs, 13 nm in diameter) as highly effective inhibitors for human immunodeficiency virus type 1 reverse transcriptase (HIV-1 RT). Two Apts, RT1t49 (Aptpol) and ODN 93 (AptRH), which recognize the polymerase and RNase H regions of HIV-1 RT, are used to conjugate Au NPs to prepare Aptpol-Au NPs and AptRH-Au NPs, respectively. In addition to DNA sequence, the surface density of the aptamers on Au NPs (nApt-Au NPs; n is the number of aptamer mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 90 publications
0
37
0
1
Order By: Relevance
“…Schematic representation of the binding and enzymaticactivity of HIV-1 RT toward poly(rA):oligo(dT)12-18 A) in the absence and B) in the presence of aptamer-AuNPs. [136] ChemBioChem 2016, 17,1052 -1062 www.chembiochem.org…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schematic representation of the binding and enzymaticactivity of HIV-1 RT toward poly(rA):oligo(dT)12-18 A) in the absence and B) in the presence of aptamer-AuNPs. [136] ChemBioChem 2016, 17,1052 -1062 www.chembiochem.org…”
Section: Discussionmentioning
confidence: 99%
“…[135] Shiang et al showedt hat these two aptamers-conjugated AuNPs (each 13 nm in diameter) are highly effective inhibitors for HIV-1 RT, with their designp rincipless hown in Figure 8. [136] They found that the loading density of aptamersa nd the linker length between the aptamer and AuNPs both play important roles in determining their inhibition activity.W hen 40 ODN 93 aptamers were conjugated onto the surface of AuNP with aT 45 linker length,t he aptamer-AuNPc omplexes showedi nhibitory efficiency in the retroviral replication cycle, with ar educed infectivity of 40.2 %.…”
Section: Antiviral Aptamer-aunpsmentioning
confidence: 99%
“…Very few approaches using AuNPs as carrier for anti-HIV drugs have been reported [30,31]. Our groups tested in a previous work that AuNPs conjugated to a CCR5 antagonist, reduced viral production [13].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, aptamers that can select various proteins of HIV type 1 (HIV-1) including Rev protein [43,44], reverse transcriptase (RT) [43,45], and Tat [43] were recognized for their potential in therapeutics. Many of them have been continuously developed to inhibit the RT protein of HIV [46][47][48][49][50][51][52]. In a battle to replace antibodies destroyed by the virus, the spotlight gradually shifted to the diagnostic and therapeutic functions of aptamers in targeting immune systems [53,54].…”
Section: Aptamer Timelinementioning
confidence: 99%